Multiracial identity development experiences of Malaysian Chinese-Indian Christians - Santoadi, Fajar (2013)
Multiracial individuals are commonly found, multiracial identity development model developed in the context of Malaysia has not yet established. There is knowledge gap in this issue therefore this study was significant for multicultural counselling practice in Malaysia. Goal of this study was to explore Christian Chinese-Indian individuals’experience during the course of their development and the objectives were: (1) To explore the experiences of multiracial identity development of Christian Chinese-Indian individuals in Malaysia throughout the life span and (2) To explicate how the environmental factors bring about meaningful influence in the stage of Christian Chinese-Indian multiracial identity development. Interpretative phenomenological Analysis was employed to study conscious experiences of the respondents. Purposive sampling was used to select seven Chinese-Indian Individuals fitting to the criteria in Peninsular Malaysia. Recorded semi-structured interviews with the seven respondents and field notes were used to collect data. To ensure quality of this study,member checking, data triangulation, theory triangulation, peer debriefing or independent mini audit, and incorporating deliberate excerpt of the interview were employed. This study found that: (1) the self-identification throughout the formative period was multiple, changing, and leaning toward Chinese or Indian or ‘in the middle’ depending on the predominant peer group change; (2) multiracial identity development model that was described as unawareness period, indefinite period,transitional period, and embrasure period; (3) each social environment played roles in the multiracial identity formation i.e. the parents influenced more in identity formation as Christian but less in identity as Chinese or Indian; extended family provided exposure to the Chinese and Indian tradition; peer groups gave significant influence in mono-racial identity formation as Chinese, Indian, and Malay and multiracial identity (Chindian); the neighbourhood role was not significant; the institutions of education and contact with general public in Malaysia triggered and strengthened multiracial awareness, and promoting inclusive self-identification as Malaysian. Implication of this study is developing healthy multiracial identity in Malaysia required alteration of arbitrary monoracial of category to acknowledgement of multiracial self and counselors are called to help CCIIs developing healthy multiracial identity by individual counseling, group counseling, and psychoeducation for CCIIs and their parents.